Internet safety of children in Kazakhstan: problems and solutions - Oshanova О.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article raises the issue of legal regulation of the Kazakhstan Internet space. The author examines the issues of combining the methods of legal regulation and self-regulation on the Internet. In particular, we are talking about the fact that the threat from the Internet for children is growing every day. Prospects of soft law in the international regulation of the Internet, in countries such as the United States, Britain and Russia are assessed from different points of view. Especially the author draws attention to such topics as terrorism, pornography, and encroachment on the honor and dignity of citizens. The relevance of this topic is expressed in the fact that the Internet is still not sufficiently regulated from a legal point of view. The constant increase in the number of subscribers and the growing importance of information exchange through the Network attract the public’s attention to the problems of regulation, the development of rules for the fair, legitimate functioning of the Internet by the state. The author points out the need for legislative regulation measures on the part of the state and society in this direction, involving data on the availability of social networks in the country and their impact on children. Internet legislation is a set of laws, other normative acts (national and foreign states) which are regulating relations in the virtual space of the Internet. An Internet relationship is considered only those relations that relate to the social and legal regulation of the virtual space that is with the regulation of this space based on the norms of law, morals, ethics, and other means. The main problems of legal regulation are related to the order and conditions of the use of telecommunications networks and protection of the rights and legitimate interests of various entities during the transfer of information in global computer networks. There is a need to develop adequate national legislation with all modern requirements. At present, the domestic information legislation of Kazakhstan and other countries is very extensive. However, it is still far from perfect and requires working out and adopting new acts.